2012
DOI: 10.1186/1471-2288-12-4
|View full text |Cite
|
Sign up to set email alerts
|

A proof of principle for using adaptive testing in routine Outcome Monitoring: the efficiency of the Mood and Anxiety Symptoms Questionnaire -Anhedonic Depression CAT

Abstract: BackgroundIn Routine Outcome Monitoring (ROM) there is a high demand for short assessments. Computerized Adaptive Testing (CAT) is a promising method for efficient assessment. In this article, the efficiency of a CAT version of the Mood and Anxiety Symptom Questionnaire, - Anhedonic Depression scale (MASQ-AD) for use in ROM was scrutinized in a simulation study.MethodsThe responses of a large sample of patients (N = 3,597) obtained through ROM were used. The psychometric evaluation showed that the items met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…These results were also found in other CAT studies, such as on the Center for Epidemiological Studies-Depression Scale (CES-D), where the total scale of 20 items could be reduced to 7 items [23]. …”
Section: Discussionsupporting
confidence: 71%
“…These results were also found in other CAT studies, such as on the Center for Epidemiological Studies-Depression Scale (CES-D), where the total scale of 20 items could be reduced to 7 items [23]. …”
Section: Discussionsupporting
confidence: 71%
“…To reduce the burden imposed by lengthy outcome instruments, adaptive testing methodologies should be adopted to focus instruments on ranges of items appropriate for each individual [42]. This process could be guided by an initial assessment of each patient's basic level of activity (eg, sedentary activities; light domestic duties; light recreation and sport; intense exercise and recreation; contact sports) and then progressively refined as more activities are selected from graded subscales.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…CAT thus allows for an assessment that is tailored to the examinee taking it, with items targeted to provide information about the given examinee's unknown latent trait(s). Numerous studies have found that CAT achieves substantially greater measurement efficiency than traditional paper-and-pencil tests (Gibbons et al, 2008;Moreno, Wetzel, McBride, & Weiss, 1984;Smits, Zitman, Cuijpers, den Hollander-Gijsman, & Carlier, 2012;Weiss, 1982).…”
mentioning
confidence: 99%